A case of primary renal oncocytic tumor: Chromophobe renal cell carcinoma or oncocytoma?. Issue 1 (16th September 2022) - Matsui, Kenta; Uchida, Katsunori; Kanai, Masahiro; Asakawa, Kana; Usui, Miki; Murata, Tetsuya
Abstract : Introduction: "Other oncocytic renal tumors of the kidney" is a new category constituted by 2022 WHO classification and different in the point of morphology and immunohistochemistory from typical oncocytic/eosinophilic renal tumors including chromophobe renal cell carcinoma and oncocytoma. Case presentation: The patient was an 84‐year‐old woman in whom a left renal tumor was incidentally discovered. She underwent left nephrectomy, and the pathological specimens showed a borderline eosinophilic renal tumor between chromophobe renal cell carcinoma and renal oncocytoma. After all recognized oncocytic tumors were excluded, we diagnosed the tumor as other oncocytic renal tumor of the kidney. Conclusion: Other oncocytic renal tumor of the kidney is a provisional category. Therefore, further research and accumulation of similar cases are necessary.